Using Role Play Technique to Improve Students Speaking Skill at the Eighth Grade of SMPN 7 Bukittinggi - Precelia Gita Mulyo; Veni Roza; Melyann Melani; Reflinda Reflinda (Pusdikra-Publishing.com, 2024)
The purpose of this research was to to know whether using the role play technique can improve the students’ speaking skill. The researcher had done in SMPN 7 Bukittinggi at VIII.7 class. The problems in this research was caused by several factors. The first problem, most of the students were still awkard in speaking, the only spoke when the teacher asked them. The second problem, the lack of opportunities for students to speak when learning English in the class. The third problem, the students were less excited or less encouraged enough to participated in the speaking learned process. To obtain the research data the writer conducted the observation and test. It was found that there was a significant effect of using role play technique toward students speaking skill. It is proven that role play techniques can improve students' speaking skills. Where student scores increased further from cycle 1 to cycle 2. From the prelimenery research it can be seen that the average student score is 60,00. After carrying out actions in cycle 1 the average value increased, namely 72.25 and in cycle 2 it increased again to 91,00. It can be concluded that all the students enjoy with the role play technique. Moreover, they admitted that their speaking skill improve.